SOCIOLOGICAL PERSPECTIVES OF TERTIARY EDUCATION TRUST FUNDS’ INTERVENTION ON PROVISION OF INSTRUCTIONAL FACILITIES IN COLLEGES OF EDUCATION IN NORTH-WEST ZONE, NIGERIA (Scientific Journal of Educational Management, Research and law, 2025)
The study was on sociological perspectives of Tertiary Education Trust Funds’ Intervention on Provision of Instructional Facilities in Colleges of Education in North-West Zone, Nigeria. The design adopted for this study was descriptive survey. The population of this study comprise of all academic staff, management staff and TETFund desk officers in all the 12 public Colleges of Education in North-West geopolitical Zone of Nigeria as at May, 2021. There are 4,562 academic staff, 72 management staff and 12 TETFund desk officers totalling 4646. The sample size for this study was at 355.This includes academic staff, management staff and TETFund desk officers. The sample size is determined based on research advisors (2006) table for sample size selection. Proportionate simple random sampling technique was used. The data collection instrument for the study was self-developed structured questionnaire. The questionnaire was prepared based on Likert five-point scale. The instrument was duly vetted the by Supervisors and other relevant experts. The questionnaire was subjected to trial testing using 36 respondents from Niger State College of Education, Minna. The research question was analyzed using frequency counts; percentage, arithmetic mean and standard deviation to obtain overall average scores. Also, Analysis of Variance (ANOVA) was used to test the null hypothesis at 0.05 alpha level of significance. The study found that Tertiary Education Trust Funds Intervention has made considerable sociological perspectives on the provision of Instructional facilities such as; computers; laptops, desktops Internet connectivity, smart-board, library resources and laboratory equipment, other projects include constructions and rehabilitations of lecture theatres, classrooms, hostels, offices, laboratories, road network and fencing of institutions in different parts of Colleges of Education in North-West Zone, Nigeria. The study recommends that the TETFund and beneficiary institutions should make sure that they assign their projects to only contractors who are certified to be honest and competent and the monitoring team should be at work always to make sure that they evaluate the project at close interval.